Anterior Cruciate Ligament Reconstruction using Bone Patellar Tendon Bone autograft in ACL deficient Knee - Karn, Navin Kumar; Jha, Rajiv Kumar; Ranjan, Nashit (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: Injury to Anterior Cruciate Ligament (ACL) reconstruction has increased because of increased interest in sports. There are various grafts used for reconstruction of ACL, for example, Bone Patellar Tendon Bone, Hamstring etc. The study was conducted to evaluate the results of Bone Patellar Tendon Bone graft used for reconstruction of Anterior Cruciate Ligament. Materials & Methods: 40 patients with chronic ACL deficient knee presenting to Neuro Hospital from July 2011 to June 2013 were included in the study. The patients with intraarticular fracture of knee, severe OA knee, local active or suspected infection and systemic disease that might influence the study results were excluded from the study. Bone patellar tendon bone graft was harvested from ipsilateral knee in all the cases. The patient was followed till 2 year with specified programme of rehabilitation. The pain was assessed using VAS and the function of the knee was assessed using Modified WOMAC knee index. Results: The long term satisfactory results in terms of functional stability, symptom relief and return to preinjury level of activity was seen in 32 cases (80%). Two knees got infected out of which one required arthroscopic debridement. Mean visual analogue scale was 8 and modified WOMAC knee score was 3 at 2 year follow up. Conclusion: Bone patellar tendon bone graft is useful in high demand patients and cost effective option with high patient satisfaction rate for reconstruction of ACL. JCMS Nepal. 2015;11(3):12-15.